Don Vicente two novels - Jose, Francisco Sionil 1924- (Modern Library, 1999)
A novel on the Huk rebellion in the Philippines early this century, featuring a man who joins a peasant revolt against his father, a feudal landlord. The revolutionary attempts to persuade his half-brother to join, but the other refuses.